Modeliranje števila smrtnih žrtev pri porušitvi stavbe - Lazar Sinković, Nuša (Gradbeni vestnik, 2018)
The consequences of earthquakes cannot be completely prevented, but they can be effectively mitigated by appropriate measures, such as earthquake-resistant construction. Therefore, it is reasonable to consider the building importance category in earthquake-resistant design, as well as in seismic retrofit of existing buildings, since the consequences of damage or collapse of buildings are different from one building to another. In general, several indicators could define the building importance category. In this article, we focus on a model for the estimation of the number of fatalities given the collapse of a building, which could be used in the future as one of the indicators for determining the building importance category, since the protection of human lives is a basic objective of standards for earthquake-resistant design of buildings. The introduced fatality model takes into account the type of the building, i.e. the structural system, and a time variant population model of people present in the building during the earthquake. The use of the model for the estimation of the number of fatalities is demonstrated by means of an example of the building of the Faculty of Civil and Geodetic Engineering. In the example we adopted the population model proposed by FEMA P-58-1, based on which we predicted a peak building occupancy of 467 during the day. If an earthquake causes the collapse of the building on a weekday during working hours, the expected number of fatalities is 117. No fatalities are expected if collapse occurs during the night and 4 if the building collapses during the weekend in the daytime. The average number of expected fatalities on an annual basis is 24.
Keywords: building collapse; built environment; earthquake consequences; earthquake engineering; fatalities; grajeno okolje; porušitev stavbe; posledice potresa; potresno inženirstvo; potresno tveganje; seismic risk; smrtne žrtve